Electrochemical insights into layered La2CuO4 perovskite: Active ionic copper for selective CO2 electroreduction at low overpotential. (5th December 2019) - Singh, Rana Pratap; Arora, Payal; Nellaiappan, Subramanian; Shivakumara, C.; Irusta, Silvia; Paliwal, Manas; Sharma, Sudhanshu
Abstract: La2 CuO4, a layered perovskites oxide was synthesized using solution combustion method at different calcination temperatures. XRD characterization and Rietveld refinement analysis confirms the pure phase of the synthesized material. The effect of calcination causes shrinking in the lattice parameters affirm the change in the oxygen stoichiometry. Four Probe (Van der Pauw's) and CP-AFM analysis were carried out to understand the influences of calcination temperature on electrical conductivity. Electrochemical investigations on La2 CuO4 were performed at various negative potential ranges using cyclic voltammetry (CV) to identify the redox active centre. Thermodynamic calculations are further carried out to validate the electrochemical results in different mediums. Selective electrocatalytic conversion of CO2 to C2 -hydrocarbon (C2 H4 ) with FE% of 40.3% which is 10 times higher than CH4 (FE% = 4.1%) emphasized the in-situ formation of Cu2 O from the redox active centre present in La2 CuO4 . Hydrocarbons are generated at a very low overvoltage (−0.4 V RHE) in comparison to literature. XPS analysis indeed confirms the presence of Cu + species i.e., in-situ generated Cu2 O, on La2 CuO4 after CV and CO2 electrocatalysis. Graphical abstract: Image 108061 Highlights: In the present study, we have explored the electrochemical behavior of redox active centre 'Cu 2+ ' in a highly crystalline layered La2 CuO4 perovskite. During electrochemical reduction, La2 CuO4 breaks into La2 O3 and Cu2 O. This Cu2 O further undergo reduction and forms Cu metal which is a reversible reaction. Thermodynamic calculations aided in understanding the electrochemical in-situ formation of Cu2 O. Selective electrocatalytic reduction of CO2 to C2 H4 (10 times higher than CH4 ), at −0.4 V RHE, very low overpotential, emphasis the typical behaviour of Cu2 O. XPS analysis confirms the presence of Cu + species (i.e., Cu2 O) after electrochemical treatment of La2 CuO4 and retained after selective CO2 electrocatalysis.